Survei Kebugaran Siswa SDN Darungan 0 - Fahrian Jaya Cipta, Muhamad; Yono, Topo; Sulaiman, Ahmad (Jurnal Muara Olahraga, 2024)
Physical fitness is a person's ability or ability to complete a physical task without experiencing excessive fatigue and having the ability to do other work. Carrying out sports activities has many goals, including maintaining and improving the health and fitness of the sports person's body. Physical fitness is a physical condition that includes a person's ability to carry out daily physical activities efficiently and without too much fatigue. Physical fitness involves various aspects, including muscle strength, cardiorespiratory endurance, flexibility, balance, and coordination.This study aims to determine the level of fitness of students in grades V and VI of SDN Darungan 03, Tanggul District, Jember Regency in 2024 using a series of Indonesian Student Fitness Tests phase C. This type of research is a study using a quantitative descriptive method. The approach used in this study is a survey, with the results of the Child Ball Test obtained 4 students classified as Very Good with a presentation of 29%, 6 students classified as Good with a percentage of 43%, 2 students classified as Moderate with a percentage of 14,%, and 2 students classified as less with a percentage of 14%, the Tok-Tok Ball Test obtained 5 students classified as Very Good with a presentation of 36%, 7 students classified as Good with a percentage of 50%, and 2 students classified as Moderate with a percentage of 14%. The Move The Ball Test obtained 5 students classified as Very Good with a presentation of 14%, 7 students classified as Good with a percentage of 50%, and 2 students classified as Moderate with a percentage of 36%. The Shuttle Run 8 x 10m Test obtained, 10 students classified as Good with a percentage of 71%, and 4 students classified as Moderate with a percentage of 29%. The 600m Run Test obtained, 2 students classified as Very Good with a percentage of 14%, and 12 students classified as Good with a percentage of 86%.Keywords: Physical fitness, students, Indonesian student fitness test phase c.